Design for the New World From Human Design to Planet Design - Engholm, Ida (2023)
Design for the New World aims to introduce a new paradigm in design and design thinking, by shifting our approach from a human perspective that is primarily focused on human scales, needs, and desires, to a planet perspective, in which design is guided by the ambition to create a balanced coexistence between humans and the other species that make up the global ecosystem. The book intervenes in current discussions within design research about what role design can play in the sustainable transition, by offering new methods and mindset to handle the giant-scale complexity of the climate and environmental crisis, as well as specific tools to turn these theoretical reflections into a transformative practice. Essential reading for researchers, students, and practitioners in the fields of design, innovation, development, entrepreneurship, leadership, art, and creativity. The book is structured so that it can be easily used in an educational context, both at under- and postgraduate level and in courses of business, innovation, or management training. The practical suggestions and process-management tools can be used to facilitate sustainable transformations in in commercial businesses, organizations, and political networks. Written in an accessible and clear style, where all technical terms are fully introduced and unpacked. The chapters can be read in order or independently, and the practical tools for facilitating processes of change are supplemented with additional questions for reflection and further development.